Exploring the Influence of Digital Literacy, Metacognitive Awareness, and Prior Knowledge on Critical Thinking Skills among Engineering Education Students - Hidayat, Hendra (Jurnal Neo Konseling, 2022)
In the era of rapid technological advancement, critical thinking has become a core competency in higher education, especially within engineering education. This study investigates the influence of digital literacy, metacognitive awareness, and prior knowledge on the development of critical thinking skills among engineering education students in Indonesian universities. Using a quantitative approach, data were collected from 455 undergraduate students through validated questionnaires. The results, analyzed using structural equation modeling (SEM), reveal that all three independent variables significantly and positively influence students' critical thinking skills, with metacognitive awareness emerging as the strongest predictor. The findings highlight the importance of integrating digital competence, reflective learning, and foundational knowledge in the curriculum to foster critical thinking. This study offers theoretical and practical implications for enhancing cognitive development in higher education settings.